2015
DOI: 10.1037/xge0000028
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual homunculus: The perception of the relative proportions of the human body.

Abstract: Given that observing one's body is ubiquitous in experience, it is natural to assume that people accurately perceive the relative sizes of their body parts. This assumption is mistaken. In a series of studies, we show that there are dramatic systematic distortions in the perception of bodily proportions, as assessed by visual estimation tasks, where participants were asked to compare the lengths of two body parts. These distortions are not evident when participants estimate the extent of a body part relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 32 publications
10
85
3
Order By: Relevance
“…Interestingly, distortions of hand shape measured in localization tasks matched those found in tactile size perception of the hand (Linkenauger et al, 2015;Longo & Haggard, 2011;Weber, 1834Weber, /1996. Hand distortions measured in localization tasks were consistent with anisotropies characterizing the hand's tactile acuity and receptive field geometry , 2011.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Interestingly, distortions of hand shape measured in localization tasks matched those found in tactile size perception of the hand (Linkenauger et al, 2015;Longo & Haggard, 2011;Weber, 1834Weber, /1996. Hand distortions measured in localization tasks were consistent with anisotropies characterizing the hand's tactile acuity and receptive field geometry , 2011.…”
Section: Introductionmentioning
confidence: 61%
“…However, multiple studies indicate the presence of systematic distortions in the perception of bodily proportions (Linkenauger et al, 2015;, 2011Saulton, Dodds, Bülthoff, & Rosa, 2015). Those distortions were demonstrated in visual estimations tasks (Linkenauger et al, 2015;Longo & Haggard, 2012) as well as in tactile and localization tasks , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third possibility was recently proposed by Linkenauger et al (2015). On their interpretation, visual representations of the body show distortions directly opposite to those of somatosensory representations.…”
Section: How Are Different Distortions Related?mentioning
confidence: 98%
“…Recently, a growing literature has started to show that distorted body representations are not unique to disease, but a characteristic part of healthy perception/cognition. Indeed, numerous studies have revealed large and highly consistent distortions of body representations in healthy human adults (Fuentes, Longo, & Haggard, 2013;Hach & Schütz-Bosbach, 2010;Linkenauger, Wong, et al, 2014;Linkenauger, Witt, Bakdash, Stefanucci, & Proffitt, 2009;, 2011, 2012a, 2012bSaulton, Dodds, Bülthoff, & de la Rosa, 2015).…”
Section: Introductionmentioning
confidence: 99%